Variáveis dendrométricas da seringueira e sua relação espacial com atributos químicos do solo - Santos, Adilson Almeida dos (2015)
The rubber tree (Hevea brasiliensis) is the main species producing one of the most important agricultural commodities: natural rubber. Despite the considerable importance of this product, the rubber trees in Brazil is marked by problems related to the management of culture and incidence of pests and diseases. The low nutrient content of Latosols and high susceptibility to erosion of the ultisol, is seen as a limiting factor in the production of brazilian rubber. However, such problems can be solved with fertilization through fertilization and adoption of conservation practices. In this sense, the aim of this study was to evaluate the spatial dependence of variables dendrometric of rubber trees (hybrid Fx 3864 ) and soil chemical properties. The study was conducted in Fazenda Pedra Linda, in the municipality of Nova Venecia - ES. The soil of the experimental area was classified as Oxisol, clayey. The dendrometric variables raised in the countryside, in three different periods in 200 rubber plants were: circumference of the base of the trunk (CBT), circumference at breast height (CAP) and tree height (ALT). Seeking to characterize the fertility of the soil samples were collected through a random sample consisting of 60 sampling points at 0-0,20 m and 0,20-0,40 cm. Data were analyzed descriptively, to the dendrometric variables were correlated to soil attributes by Pearson correlation coefficients. To check and quantify the spatial dependence of the attributes and variables studied, the data were subjected to a geostatistical analysis from the theoretical adjustment functions to the models of experimental semivariogram. In analysis of correlations, K correlated significantly with all dendrometric variables in the third measurement. Another feature is the correlation between P and all variables dedrométricas the second measurement, except for the CBT. All attributes studied, except for the P in layer 0-20 cm CTC in the 20-40 cm layer showed spatial dependence. Among the variables just dendrometric CBT in the third measurement did not present spatial dependence. The geostatistical shown an effective tool for soil fertility analysis and dendrometric measures of rubber. However the sample number was not enough to match the study, the CTC, 0-0,20 m depth and CBT and DAP at 24 months of culture.